Impact of the COVID-19 pandemic on management and outcomes in acute appendicitis: Should these new practices be the norm?. Issue 5 (October 2021) - Somers, Kate; Abd Elwahab, Sami; Raza, Muhammad Zeeshan; O'Grady, Sorcha; DeMarchi, Joshua; Butt, Abeeda; Burke, John; Robb, William; Power, Colm; McCawley, Niamh; McNamara, Deborah; Kearney, David; et al.
Abstract: Background: In early 2020, the COVID-19 pandemic significantly altered management of surgical patients globally. International guidelines recommended that non-operative management be implemented wherever possible (e.g. in proven uncomplicated appendicitis) to reduce pressure on healthcare services and reduce risk of peri-operative viral transmission. We sought to compare our management and outcomes of appendicitis during lockdown vs a non-pandemic period. Methods: All presentations to our department with a clinical diagnosis of acute appendicitis between 12/03/2020 and 30/06/2020 were compared to the same 110-day period in 2019. Quantity and severity of presentations, use of radiological investigations, rate of operative intervention and histopathological findings were variables collected for comparison. Results: There was a reduction in appendicitis presentations (from 74 to 56 cases), and an increase in radiological imaging (from 70.27% to 89.29%) ( P  = 0.007) from 2019 to 2020. In 2019, 93.24% of patients had appendicectomy, compared to 71.42% in 2020( P  < 0.001). This decrease was most pronounced in uncomplicated cases, whose operative rates dropped from 90.32% to 62.5% ( P  = 0.009). Post-operative histology confirmed appendicitis in 73.9% in 2019, compared to 97.5% in 2020 ( P  = 0.001). Normal appendiceal pathology was reported for 17 cases (24.64%) in 2019, compared to none in 2020 ( P  < 0.001) – a 0% negative appendicectomy rate (NAR). Discussion: The 0% NAR in 2020 is due to a combination of increased CT imaging, a higher threshold to operate, and is impacted by increased disease severity due to delayed patient presentation. This study adds to growing literature promoting routine use of radiological imaging to confirm appendicitis diagnosis. As we enter a second lockdown, patients should be encouraged to avoid late presentations, and surgical departments should continue using radiological imaging more liberally in guiding appendicitis management. Highlights: Incidence and severity of acute appendicitis presentations during COVID19 pandemic. Compulsory radiological confirmation of acute appendicitis prior to appendicectomy. Operative vs Non-operative management of acute appendicitis during COVID19 pandemic. Conservative management of radiologically confirmed uncomplicated appendicitis. Increased imaging in acute appendicitis and decreased negative appendicectomy rate.